(untitled) (REMUNOM, 2024)
The use of anabolic steroids (AES) has grown significantly in recent years. The achievement of the perfect body and the search for the highest place on the podium, under the influence of social media, means that people, mostly young people, practice this risky and often harmful attitude. Certain medications considered safe to use are used inconsequentially and in high doses. This bibliographical review aims to alert readers about the damage caused by the use of steroids and anabolic steroids, and also the possible and dangerous cardiac injuries associated with dyslipidemic changes that act in association with future clinical conditions. The present study is an integrative literature review, using as research sources articles obtained from the electronic databases Google Scholar, Scientific Electronic Library Online (Scielo), and Pubmed, using the following keywords: anabolic, hormones, bodybuilding, steroids, health, effects, testosterone, and stanozolol